Health misinformation, digital health literacy, and attitudes toward science among university students: an exploratory cross-sectional survey - Adele Sarcone; Claudia Pileggi; Carmelo Nobile; Silvio Simeone; Caterina Mercuri (Frontiers in Public Health, 2026)
Background The spread of health misinformation through digital platforms poses an increasing challenge for public health. University students are among the most exposed groups, given their heavy reliance on online environments for health-related information. Objective This study investigated health information sources, digital health literacy skills, criteria for evaluating information quality, use of homeopathic and alternative remedies, and attitudes toward science among students at the University Magna Graecia of Catanzaro (UMG), Italy. Methods An exploratory cross-sectional survey was conducted on 407 UMG students (277 females, 68.06%; mean age 23.23 ± 6.15 years), enrolled in Nursing (65.36%), Medicine and Surgery (23.34%), Engineering (2.46%), and other programmes (8.85%). Data were collected via a structured self-administered questionnaire distributed through Google Forms. Descriptive statistics, independent-samples t -tests, chi-square tests, and stepwise logistic regression were performed. Results Social media was the most frequently used health information source (75.43%), yet only 12.78% of students considered it reliable. The physician was identified as the most trustworthy source by 94.10% of participants. Basic digital health behaviors were common, but advanced self-reported critical evaluation abilities were markedly limited: only 15.72% self-reported the ability to critically select online health content. Attitudes toward science were generally positive. Chi-square analyses revealed sex differences in response distributions for several items, and logistic regression showed that female sex was positively associated with sensitivity to the ethical dimension of scientific work (OR = 1.61). Conclusions Positive scientific attitudes coexisted with underdeveloped self-reported critical evaluation abilities. These findings support the integration of digital health literacy training into university curricula to better prepare students to navigate the contemporary infodemic environment.